Peranan Kepuasan Kerja Dalam Memediasi Pengaruh Kompensasi Terhadap Loyalitas Karyawan Pada Pt Parama Asia Sejahtera - Putu Dita Saptarini; Ni Made Yudhaningsih (Jurnal Ilmiah Satyagraha, 2020)
The purpose of this study is to determine the role of job satisfaction in mediating the effect of compensation on employee loyalty at PT Parama Asia Sejahtera.  This study uses a saturated sample method with 35 employees of PT Parama Asia Sejahtera as the sample.  The analysis technique used in this study is path analysis which is accompanied by a Sobel test.  Based on the results of the analysis, we can find that compensation has a positive and significant effect on employee loyalty, compensation has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee loyalty and job satisfaction mediates the effect of compensation and employee loyalty on PT Parama Asia Sejahtera.  Based on the results of the study, it was found that the direct effect of compensation on employee loyalty amounted to 0.465 or 46.5%, the effect of compensation on job satisfaction was 0.869 or 86.9% and the effect of job satisfaction on employee loyalty was 0.584 or 58.4% while indirect compensation effects  towards employee loyalty through job satisfaction of 0.507 or 50.7% greater than the direct effect of compensation on employee loyalty so that job satisfaction is able to mediate the effect of compensation on employee loyalty at PT Parama Asia Sejahtera.  From the results of the research, the management of PT Parama Asia Sejahtera should pay more attention to the compensation given to employees by providing more appropriate compensation and give some period for a furlough to their employees.